2002
DOI: 10.1556/aphyt.37.2002.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Attractants for Females of Pest Pyralids and Phycitids  (Lepidoptera: Pyralidae, Phycitidae)

Abstract: In field trapping tests conducted in Hungary large numbers of Pyralis costalis F. (Lepidoptera: Pyralidae), a secondary pest, were attracted to traps baited with iso-amyl alcohol (3-methyl-1-butanol) and acetic acid. The same bait attracted lower numbers of P. farinalis L., a well-known stored product pest. In both spp. the capture of the two-component blend was significantly higher than the catch in traps with the single components. In tests conducted in a country mill, the blend of the above two compounds pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
(2 reference statements)
2
21
1
Order By: Relevance
“…If, however, attractive substances can lure and catch females, monitoring females may become an additional and accurate measure during mating disruption trials, since females are not affected by synthetic sex pheromones. Many studies have investigated food‐derived compounds for female orientation to oviposition sites, and the results have varied depending on the species investigated 25–28…”
Section: Discussionmentioning
confidence: 99%
“…If, however, attractive substances can lure and catch females, monitoring females may become an additional and accurate measure during mating disruption trials, since females are not affected by synthetic sex pheromones. Many studies have investigated food‐derived compounds for female orientation to oviposition sites, and the results have varied depending on the species investigated 25–28…”
Section: Discussionmentioning
confidence: 99%
“…Traps The standard CSALOMON® VARL + funnel traps, produced by the Plant Protection Institute, HAS (Budapest, Hungary) (Tóth et al 2000(Tóth et al , 2002Subchev et al 2003) were used. This trap consists of an opaque plastic funnel (top opening, 13 cm o.d., funnel-hole diam., 3 cm, height of funnel, 16 cm), with a 20 × 20 cm flat, plastic roof, and a transparent plastic round container (ca 1 l, held in place by a rubber band).…”
Section: Methodsmentioning
confidence: 99%
“…One or three lures were used in the traps to test for effect of lure concentration. Lures in traps were changed at 2-3 wk intervals, as previous experience with similar lures showed that they may lose activity after this period (Tóth et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Previous results with acetic acid tested against other pests showed that this type of dispenser was active for several weeks of field exposure (i.e. Tóth et al, 2002); hence, we decided to renew the lures at 2-to 3-week intervals.…”
Section: Polyethylene Bag (Pe Bag) Dispensers (For Acetic Acid and Acmentioning
confidence: 99%